Northern Civilization Corridor in the Eurasian Socio-Cultural Space: Statement of the Problem - Andrey V. Ivanov; Yuri V. Popkov (Арктика и Север, 2025)
The article substantiates the important role of the Arctic zone of Russia in forming and strengthening not only its geopolitical, defense, resource and raw material, economic, transport and communication potential, but also as a significant civilization corridor, providing intensive interaction between different peoples and cultures, which goes far beyond the boundaries of this particular region. Civilization corridors are understood as the basis for the functioning of individual territorial locations, linking them into a living and developing organism of a single humanity due to their fulfillment of the most important migration, communication, information, trade and political socio-cultural functions. There are latitudinal and me-ridional civilization corridors in the Eurasian socio-cultural space, the intersections of which form the cen-ters of civilizational dialogue of various political, ethnic and religious communities. The three most im-portant latitudinal civilization corridors are the Great Silk Road, the Trans-Siberian Railway (Transsib), and the fundamental conclusion is substantiated about the possibility and exceptional importance for Russia and the whole world of turning the existing Arctic sea transport route into a new civilization corridor that is able to link not only the civilizations of the East and West into a single system of Eurasia, but also North and South. The article analyzes the objective prerequisites for the formation of this new and “youngest” civilization latitudinal corridor, as well as its unifying civilizational functions. The historical role of the Russian people, who united the peoples of the North into a single local Arctic civilization, possessing the civilizational gift of peaceful exploration of space through organic “ingrowth” into other ethno-cultural worlds, is emphasized. The civilizational approach in the unity of its synchronic and diachronic dimensions is used as the main methodological resource of the study.